The Retail -Investors perception towards investment in the Liberalized era - A case study of Trivandrum city - Rao, P. Kameswara; Prahhu, N. R. V. (Gyan Management Journal, 2007)
This paper examines the determinants of retail investors and private corporate investment in India with emphasis on the implications of the policy reforms of liberalization. The result,;; suggest that the net impact of the liberalization on retail investors' perception is tremendous. The adverse impact of the decline in public investment has been outweighed by the positive effects of the decline in the cost of capital and favorable changes in investor perception brought about by the reforms. While it is not possible to generalize from a single country case, our results cast doubt on the existing cros·scountry evidence of a negative impact of structural adjustment reforms on private investment and also the case example of Trivandrum·city.
Keywords: Retail -Investors; Liberalized era; Trivandrum city; S/rucwml Acljustmen/ Programme